The impact of Facebook live streaming advertisements on purchase intention - Koo, Siew Wah; Tan, Cherng Yih (2022)
The aim of our study is to investigate the impact of Facebook live streaming advertisements on purchase intention. Our study independent variables (IV) including informativeness (IN), entertainment (EN), irritation (IR) and credibility (CR) are used to examine whether they can influence on dependent variable (DV) which is Facebook live advertisements on consumer’s purchase intention. There are total of 384 sets questionnaires were successfully collected for our study, and all collected data were analyzed by the Statistical Software Package for Social Sciences (SPSS) software. The reliability test, Pearson’s correlation coefficient analysis and multiple regression analysis had been used to illustrate the relationship between the four IVs and DV. Besides, the results obtained for this study show the three IVs including informativeness, entertainment and credibility have a significant relationship with DV Facebook live advertisements on consumer’s purchase intention, except irritation has no significant with DV. This study provides valuable information to researchers to have more understanding on how Facebook live streaming advertisements influence the consumer’s purchase intention and adopted some knowledge to improve their business or study.